ANALISIS ASPEK FINANSIAL KELAYAKAN INVESTASI PENDIRIAN PABRIK MINYAK GORENG DI KAWASAN INDUSTRI KEMINGKING PROVINSI JAMBI - Sampor Ali; Darto Darto (Universitas Muhammadiyah Jakarta, 2022)
As one of the largest palm oil producers in Indonesia, Jambi should have a palm oil downstream industry. This study aims to determine the feasibility of establishing a Palm Cooking Oil Factory in Jambi. In determining the feasibility of investing in a cooking oil factory, a financial aspect analysis is carried out, which consists of an analysis of Capex, Opex, Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI). The results of the analysis from the financial aspect indicate that the establishment of a palm cooking oil factory is declared feasible with a project life of 10 years at a discount rate of 8.7%. The analysis of the eligibility criteria resulted in a Payback Period (PP) for 8 months 7 weeks, a Net Present Value (NPV) of Rp.1,313,277.385,474,- Profitability Index (PI) value of 1.05% and an Internal Rate of Return (IRR) of 17.45%